Sekolah Minggu dan Era Teknologi: Strategi Menghadapi Peluang dan Tantangan Digitalisasi - Mersi Nantaria Telaumbanua; Nehemia Nome (PT. Penerbit Tiga Mutiara, 2026)
The development of digital technology has brought significant changes to Sunday School ministry and children’s faith education in the modern era. Children, as digital native generations, are increasingly connected to visual media, audiovisual content, and internet use, causing conventional learning methods to become less engaging and less effective in fostering active learner participation. This study aims to analyze Sunday School strategies in addressing the opportunities and challenges of digitalization, the utilization of digital media for children’s spiritual growth, and the roles of teachers, churches, and families in developing relevant and transformative spiritual learning. The research employed a qualitative approach with a library research design enriched through phenomenological analysis of digitalization practices in Sunday School ministry. Data were obtained through a review of literature on Christian educational theology, child pedagogy, digital literacy, and reflective observation of the use of Bible animation videos, social media, and online learning platforms. The findings indicate that the digitalization of Sunday School ministry through Bible animation videos, YouTube, Zoom, Google Meet, and Christian learning applications enhances children’s interest, participation, and understanding of God’s Word through learning experiences that are more interactive, communicative, and contextual. The challenges of digitalization are reflected in gadget-related distractions, digital dependency, reduced learning concentration, and unequal access to technology among certain families. The study concludes that the success of digital Sunday School requires the integration of technology, teacher competence, parental guidance, digital literacy, and continuous spiritual formation. The novelty of this study lies in the development of a digital Sunday School ministry model that integrates technological media, pedagogical strategies, family supervision, and children’s spiritual formation in a holistic manner, thereby ensuring that church ministry remains adaptive, inclusive, and centered on children’s faith development in the digital era.